(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Education, Freedom and Inequity in the Context of the Current Challenges of Artificial Intelligence and Sustainability.In the current context of the challenges generated on the one hand by multiple crises, and on the other hand by the current digital and green eras, the general principles governing the Convention on the Rights of Persons with Disabilities, 2007, are among the most present in all programs and strategies at the level of the states, education, freedom and inequity, being the most sensitive themes due to the impact they have on the economies of the states. Moreover, a figure from 2021, namely approximately 1.3 billion people - approximately 16% of the total global population - facing significant disabilities, attracts our attention, which leads us at our level of research in the financial field to seek to develop innovative financing tools that support these vulnerable people towards a normality, including using innovative artificial intelligence tools bothfor education and for the outcome of medical problems. Therefore, in this paper, we propose to highlight the elements of both global regulation and innovative solutions regarding the direct support of these people in need and in accordance with the principles of ACID (atomic, coherent, innovative and sustainable).